PERBANDINGAN MORTAR BERPASIR PANTAI DAN SUNGAI - Wahyudi, Yusuf (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
The use of sand beach as building material is very rarely used because considering the possibledamage toward the other building materials that caused by salt content in it. This research is aimedto provide an overview comparison of mortar with sand beach and Brantas River, and also the useof cement type Ordinary Portland Cement (PC) and Portland Pozzoland Cement (PPC).The result of this research showed that the average weight of sand beach is 1.7739 ton/m3,the average of dry density: 2.55, the avarege of SSD density: 2.63, the average of appearancedensity: 2.83, the average of absorption: 2.16%. The value of sand silt in Sendang Biru beach is1.452%, while for Brantas River is 1.424%. The best compressive strength of mortar was showedby the mixing of 20% of pp Sendang Biru and 80% of ps Brantas River, that is 318,479 kg/cm2, orabout 28.5% bigger than mortar control (1pc cement: 3ps Brantas) that is 247,706 kg/cm2.Furthermore, the compressive strength of pc mortar cement substituted by sand beach is decreaseto 68%, 25%, and 22%, while for the mixing of pp Sendang Biru compared with ps Brantas60%:40%, 80%:20%, and 100%:0%. The average compressive strength of pc cement mortar ishigher than the average compressive strength of ppc cement mortar in 28 days. The compressivestrength of mortar 1pc: 3 sand in the mix of 100% ps Brantas pc cement is 373.2 kg/cm2. Furthermore,the compressive strength of mortar subtitued with sand beach 20%, 40%, 60%, 80%, and 100%each is decreased to be 97.4%, 74.5%, 58.2%, 31.5%, and 22.8% from value control.Keyword: characteristic, compressive strength, mortar, sand beach, Portland cement, pozzolancement.